Chapter 1: Principles of Clinical Pharmacy (Foundations in Clinical Pharmacy Practice, 2025)
AuthorMr. Sri Venkatesh Uriti, Associate Professor, Department of Pharmacology, Sri Sivani College of Pharmacy, Etcherla, Srikakulam, Andhra Pradesh, IndiaAbstractClinical pharmacy has evolved from traditional dispensing functions to direct patient care, emphasizing medication optimization through collaborative practice. Pharmacists now serve as essential healthcare team members across diverse settings including hospitals, ambulatory clinics, community pharmacies, and long-term care facilities. Core competencies encompass medication therapy management, clinical decision-making, patient education, and systems-based practice. The profession requires advanced knowledge in pharmacotherapy, pathophysiology, pharmacokinetics, and communication skills. Interprofessional collaboration with physicians, nurses, and allied health professionals has become fundamental, with pharmacists contributing specialized medication expertise while respecting team dynamics. This patient-centered approach has demonstrated significant improvements in medication safety, therapeutic outcomes, healthcare costs, and quality measures, positioning pharmacists as indispensable members of modern healthcare teams focused on optimal medication use.Keywords: Medication Therapy Management, Collaborative Practice, Pharmaceutical Care, Clinical Competencies, Interprofessional TeamsVIEW PDF